Red fruit oil supplementation fails to prevent oxidative stress in rats - Maria Dara Novi Handayani; Parwati Abadi Soekarno; Septelia Inawati Wanandi (Faculty of Medicine, Universitas Trisakti, 2013)
BACKGROUNDRed fruit oil (RFO) is popular in Indonesia especially in Papua. It is consumed by people for maintaining health and to treat diseases. Red fruit (Pandanus conoideus Lam) oil is reported to contain the antioxidants á-tocoferol and âcarotene.The aim of this study was to confirm the protective effect of RFOagainst decreased glutathione levels in the plasma and liver of rats induced by 2N-(2-fluorenyl) acetamide (2-FAA).METHODSWistar male rats weighing 200 ± 20 g were randomly assigned into a control group (receiving distilled water only) and three intervention groups, designated RFO, FAA, and RFO-FAA (n=6 rats per group). RFO was given RFO 10 ì l/g/BW/day, FAA received fluoroenylacetamide (FAA) at 40ìg/day, while RFOFAA received both RFO and FAA. At 4 weeks blood samples were taken from the tail. At 8 weeks the rats were sacrified for collection of blood and liver tissues. Ellman’s method was employed to determine the parameters of antioxidantglutathione (glutahione sulfhydryl/GSH). One-way ANOVA and Tukey post hoc test were used to compare glutathione levels between groups.RESULTSThis study showed that liver and plasma glutathione levels were not significantly lower in the RFO-FAA group than in the FAA group. Glutathione levels were significantly lower in plasma and liver homogenates of the RFO group compared with the control group and were not significantly different from those in theFAA group.CONCLUSIONAdministration of RFO in rats does not protect against decreased glutathione but is a potential source of oxidative stress.